Clinical significance and expression of SLC35F6 in bladder urothelial carcinoma - Jinling Zhang; Siqi Liu; Meng Wu; Wenyu Shi; Yihong Cai (Diagnostic Pathology)
Abstract Background SLC35F6 negatively regulates outer mitochondrial membrane permeability and positively regulates apoptotic signaling pathways and cell population proliferation. The biological function of SLC35F6 in bladder cancer (BC) remains inadequately established. This study evaluates the expression and clinical significance of SLC35F6 in BC, assesses its prognostic value and explores its relationship with key immune-related molecules in the tumor microenvironment. Methods Combining bioinformatics tools and immunohistochemistry (IHC) analysis, the expression of SLC35F6 was analyzed through IHC in the tissues of 145 BC patients treated at the Affiliated Hospital of Nantong University from 2004 to 2009. The relationship between SLC35F6 expression levels and significant clinicopathological factors was examined using the chi-square test. Prognostic values were analyzed using the COX regression model and the Kaplan-Meier survival curve. Analysis of the receiver operating characteristic curve was conducted to assess the predictive performance of SLC35F6 in BC patients. Results The expression levels of both SLC35F6 mRNA and protein were elevated in BC tissue relative to benign tissue. Kaplan-Meier analysis indicated that patients exhibiting elevated SLC35F6 protein expression had a worse prognosis. Multivariate Cox regression analysis confirmed that SLC35F6, TNM stage and grade are independent risk factors for bladder cancer. SLC35F6, when analyzed alongside clinical pathological factors, enhances the accuracy of survival predictions for Bladder Urothelial Carcinoma (BLCA) patients. Conclusion SLC35F6 is upregulated in BC patients compared to normal individuals and is linked to a worse prognosis. SLC35F6 analyzed alongside clinical pathological factors can enhance the accuracy of survival predictions for BLCA patients, suggesting its potential value as a prognostic and predictive biomarker.